Potensi Penyediaan Air Bersih Berkelanjutan melalui Pemanenan Air Hujan (Studi Kasus Pulau Pasaran Kecamatan Teluk Betung Timur Kota Bandarlampung) - Jannah, Humaira Nisaul; Purwadi, Ofik Taufik; Fajar, Mutiara (Universitas Lampung, 2021)
The people of Pasaran Island, Kota Karang Village, Teluk Betung Timur District, Bandar Lampung City in their daily activities rely on clean water distributed by PDAM Way Rilau with a relatively small discharge. Population growth every year will increase the amount of water demand. This study aims to determine the potential of harvesting rainwater as an alternative to fulfill water sources on Pasaran Island. In this study, projection calculations, spatial analysis, hydrological analysis calculations, and water quality laboratory tests were carried out. The calculation results show that the water needs of the people of Pasaran Island in 2030 are 230,75 m3/day with the potential for rainwater that can be accommodated at 5.477,76 m3/day. The quality of rainwater on Pasaran Island has met the quality standards based on the Regulation of the Minister of RI Number 416/MENKES/PER/IX/1990. So that it shows that rainwater on Pasaran Island has the potential to be used as an alternative to fulfill the community's clean water.